Development of evaluation system of sailing performances on water for Japanese Olympic sailing team - Hagiwara, M.; Katori, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: During sailing races and training, the performance changes from hour to hour depending on weather and marine condition. Therefore, it is extremely difficult to evaluate the detailed sailing performance accurately on water. The primary purpose of this study was to obtain evaluation index, which would be useful for athletes and coaches in improving their sailing performances. The second aim of this study was to develop an evaluation system for obtaining the index described above. Methods: Athletes of four Olympic classes of sailing (470, RSX, Laser, and Laser Radial) and their coaches attended the National Training Camp. The camps were held three times. In the first camp, we discussed about important indices of sailing performances on water with the athletes and the coaches. We tried creating two types of our own system software with Global Positioning System (GPS), using the indices obtained from discussion in the first camp. In the second and the third camp, we supported the athletes and coaches using the system we developed. Then, we discussed again about the software for improvement, and modified it by trial and error. Results: As a result of our discussion with the athletes and the coaches, we obtained the important indices of performances related to sailing for the athletes and the coaches, and those were classified into two categories. The first of these was related to comprehensive assessment of the sailing race. Another one focused on Boat/Board speed (BS) during sailing. We created our own two system software with GPS as suitable for these categories. The classified indices were described below. 1. Index of performances related to sailing race 1) Stating performances (Speed, Timing, Positioning) 2) Performances of Up/Down-wind (Average speed and distance for Top/Bottom-mark, Tacking/Gybing, Strategy, Tactics) 3) Mark rounding (Positioning, for study of rule in the mark area) 2. Index of performances related to BS during sailing 1) A detailed assessment of BS (Velocity Made Good: VMG) Discussion: As a result, evaluation indices were classified into two categories; the index related to sailing race, and the index of performances related to BS during sailing. Therefore, it was necessary to create two types of evaluation system software to evaluate sailing performances on water. Actually, we used these systems for the athletes and coaches during the camp. They expressed positive opinions on these systems. We think that the most important parts of this study were having exhaustive discussions with the athletes, coaches, and the specialized scientist of sailing. In the future, it is expected that these systems are used daily to accumulate various data for evaluation of training effect.